Constructing Realistic Mathematics Learning Assisted by Augmented Reality Technology to Improve Students' Mathematical Creative Thinking Ability Students' Mathematical Creative Thinking - Fadila Annura Hurulean; Bety Miliyawati (Yayasan Adra Karima Hubbi, 2024)
This article presents the results of quasi-experimental research with posttest control group design that examines the context of realistic mathematics assisted by Augmented Reality Technology (ART) on students' mathematical creative thinking skills. The population in this study were all public elementary school students in Ternate City. The sample involved 110 fourth grade students from two high and medium school level elementary schools. The instruments used were initial mathematical ability test, mathematical creative thinking ability test and student attitude scale. The research data for pretest, post-test, and normalized gain scores of mathematical creative thinking ability were analyzed by two-way ANOVA and Mann-Whitney and post hoc test of One-Way ANOVA. The assumptions of normality and homogeneity of variance were performed first before using this combined statistical test. The results showed that students who received learning through Realistic mathematics context assisted by Augmented Reality Technology (ART) were significantly superior to the improvement of mathematical creative thinking skills compared to students who received Ordinary Learning (OL). The results of this study also found that there was no interaction between Mathematical Creative Thinking Ability (MCTA) and students' attitude scale in terms of both school levels.